Power, politics, and the fragmentation of evangelicalism : from the Scopes trial to the Obama administration - Collins, Kenneth J. (Downers Grove, Ill. : IVP Academic, 2012)
Kenneth J. Collins tells the narrative history of the political and cultural fortunes of American evangelicalism from the late nineteenth century through the contemporary era. He traces the establishment of the evangelical enterprise in American culture and its influences on the political and social values of the American landscape throughout the twentieth century, as well as its fragmentation into competing ideological camps. --from publisher description
Cultural shifts, the rise of Fundamentalism and the great reversal -- Fundamentalism, Neo-Evangelicalism and the search for power -- Evangelicals, the Religious Right and the moral life of the nation -- Evolution, intelligent design and the transformation of culture? -- The resurgence of the Evangelical Left -- Beyond ideology: the renewal of Catholicity and the challenges of a modern, liberal, democratic state -- Conclusion: What kind of power?
Includes bibliographical references (pages [261]-277) and indexes.
Description based on print version record.
Keywords: United States -- Church history; Evangelicalism -- United States -- History; Evangelicalism; United States; RELIGION / Christianity / History; Church history; History; Electronic books